Randomized Controlled Trial Comparing Primary and Staged Basilic Vein Transposition - Kakkos, Stavros K.; Tsolakis, Ioannis A.; Papadoulas, Spyros I.; Lampropoulos, George C.; Papachristou, Evangelos E.; Christeas, Nikolaos C.; Goumenos, Dimitrios; Lazarides, Miltos K. (Frontiers in Surgery, 2015)
Objective: It is unclear if brachio-basilic vein fistula should be performed as a primary or staged procedure, particularly for smaller basilic veins. Our aim was to report on a randomized-controlled trial comparing these two techniques. Methods: Sixteen patients with a basilic vein ≥2.5mm were randomized into primary transposed brachio-basilic vein (TBBV) fistula (n=9) and staged TBBV fistula (n=7). Patients with basilic veins enlarged by previous arteriovenous fistulas were excluded. Baseline characteristics of the two study groups, including vein size, were comparable (median basilic vein diameter 3.5 mm, range 2.8-4.1 mm). The staged group had a brachio-basilic vein fistula performed first followed by the transposition procedure performed at least 6 weeks later to allow the basilic vein to enlarge. TBBV fistula maturation at 10 weeks, primary, assisted-primary, and secondary patency were the primary outcome measures. Early failures were included in the calculation of patency rates. Results: TBBV fistula maturation rate after primary procedures (3/9, 33%) was lower compared to maturation rate after staged procedures (7/7, 100%, P=0.011, Fisher’s exact test), which led to premature termination of the trial. Time to hemodialysis [median (interquartile range)] of primary and staged procedures was 54 (51.5-113.5) days and 97 (93-126) days, respectively (P=0.16). One-year primary and assisted-primary patency rates of primary and staged procedures were equivalent (44% vs 57%, P=0.76 and 44% vs 71%, P=0.29, respectively), however, there was a trend towards a better one-year secondary patency after staged procedures (86% vs 44% for primary procedures, P=0.09). Conclusions: Among candidates for TBBV fistula with a small basilic vein, staged transposition achieves higher maturation rates compared to primary procedures, a difference reflected in long-term secondary patency. Trial registration: www.ClinicalTrials.gov, identifier NCT01274117.